EVALUASI PELAKSANAAN KEBIJAKAN PERUMUSAN UPAH MINIMUM KOTA BEKASI TAHUN 2010 - Diana Fajarwati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2011)
Objective of this studi is to assess whether the formulation Minimum Wage policy for 2010 in Bekasi has been implemented in accordance with laws and government regulations, and to know how many companies in Bekasi who unable to implement the Minimum Wages that have been set by the Governor. The research method used is descriptive evaluative method. Descriptive research methods intended to describe the nature or characteristics of a particular phenomenon that is the process of formulation of the Minimum Wage in the City of Bekasi and then evaluated whether it is in accordance with the laws and government regulations relating to minimum wage. Minimum Wage policy formulation Bekasi in 2010 has not been fully implemented in accordance with laws and government regulations